Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors